Bridgeless PFC single ended primary inductance converter in continuous current mode - Nor Akmal Rai; Mohd Junaidi Abdul Aziz; Mohd Rodhi Sahid; Shahrin Md. Ayob (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
This paper presents bridgeless single ended primary inductor (SEPIC) converter operated in continuous conduction mode (CCM). The converter used in the study offers a lesser conduction loss compared to the other bridgeless SEPIC converter.   In order to regulate the required output current and output voltage with high efficiency while achieving high power factor correction (PFC) at the input side, average current mode control (ACMC) is applied. The model is simulated using MATLAB/Simulink and it is found that the converter and the proposed control strategy provide a promising result. The preliminary results obtained from the experimental test-rig shows a good agreement as in simulation. The theoretical analysis of the proposed controller is verified on an output 100V to 300W prototype.